Anemia Profile in Cancer Patients at Adam Malik Hospital for the Period June 2022 to May 2023 - Beneditto Alfinus Sihombing; Batubara, Chairil Amin; Anggreiny; Syahrini, Heny (TALENTA Publisher, Universitas Sumatera Utara, 2024)
Background: Cancer is a condition of rapid and uncontrolled cell growth. Anemia in cancer patients is a condition that will worsen the quality of life and prognosis of cancer patients. The study aimed to determine the incidence, severity of anemia, and characteristics of cancer patients who experience anemia at the Adam Malik Hospital for the period June 2022 to May 2023. Methods: This study is a descriptive study with a retrospective cross-sectional approach. Using 97 samples of medical record data of cancer patients with the subject of cancer patients. The analysis used was univariate. Results: This study involved 97 cancer patients, there were 67 (69.1%) patients who experienced anemia, including 14 (20.9%) people with a mild degree of anemia, 33 (49.3%) people moderate degree, and 20 (29.9%) people severe degree. Of the 67 cancer patients who experienced anemia, the dominant anemia occurred in female patients as many as 38 (56.7%) people with an adult age group (18-44 years) as many as 31(46.3%) people diagnosed as hematological malignancies as many as 34 (50.7%) people with nutritional status in the normal weight group as many as 27 (40.3%) people, and as many as 46 (68.7%) people cancer patients who experienced anemia did not have comorbidities. Conclusion: Most cancer patients experienced anemia of moderate degree (69.1%), female gender, with adult age group (18-44 years), diagnosed as hematological malignancies, with nutritional status normal weight group, and had no comorbidities